First aid education for minor accidents in the family - Athia Fidian (Universitas Muhammadiyah Magelang, 2024)
First aid education for minor accidents within the family plays a crucial role in enhancing safety and preparedness in everyday life. This community service activity aims to equip mothers, who have an important role in the family, with the knowledge and skills to handle minor injuries such as cuts or minor bleeding and burns. By providing appropriate and prompt responses, family members can prevent complications and reduce the severity of injuries. First aid education also enhances a sense of security and confidence, ensuring that individuals can effectively manage emergency situations until professional medical help arrives. The methods for this activity include lectures, demonstrations, discussions through Q&A sessions, and practical exercises. The results show that mothers understand the proper handling of minor bleeding and burns as first aid measures. These results are evidenced by practical exercises performed according to the handling procedures based on real case scenarios.